Examining Culture's Impact on the Learning Behaviors of International Students from Confucius Culture Studying in Western Online Learning Context - Kang, Haijun; Chang, Bo (Journal of International Students, 2016)
There is a lack of shared understanding of how culture impacts learning in online environment. Utilizing document analysis, the authors in this research study culture’s impact on the learning behaviors of student sojourners from Confucius culture studying in Western online learning context. The shared understandings of Confucius culture and Western culture are compared, contrasted, and synthesized through Hofstede’s cultural dimensions theory. The learning behaviors of student sojourners from Confucius culture are examined from the following three dimensions: teacher-student relationship, curriculum development, and teaching and learning pedagogy. Practical implications of the findings are discussed.